2003
DOI: 10.1139/t02-116
|View full text |Cite
|
Sign up to set email alerts
|

Soil–atmosphere modelling of an engineered soil cover for acid generating mine waste in a humid, alpine climate

Abstract: A research program studying the performance of soil covers at the Equity Silver Mine was initiated in 1992. This site is situated in the humid, alpine climate of north central British Columbia. A one-dimensional, fully coupled heat and water transport, soil–atmosphere flux model was developed as part of this research program to simulate the movement of liquid water and water vapour within a soil cover in response to rainfall and evapotranspiration. Predicted and measured conditions in the cover showed good agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…At stand scale, it has been shown that high spatial variability and clustered fine root systems reduce root water uptake compared to uniformly distributed root systems (Liedgens and Richner 2001;Pardo et al 2000). While root vertical distribution is a key input in most soil-plant-atmosphere models (Eamus et al 2006;Swanson et al 2003), high lateral variability of fine roots may need to be accounted for in models for systems like the one studied here. For instance, using root data based on a few samples for such a heterogeneous system may entail substantial uncertainties in results of water balance simulations for certain artificial vegetation ecosystems.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…At stand scale, it has been shown that high spatial variability and clustered fine root systems reduce root water uptake compared to uniformly distributed root systems (Liedgens and Richner 2001;Pardo et al 2000). While root vertical distribution is a key input in most soil-plant-atmosphere models (Eamus et al 2006;Swanson et al 2003), high lateral variability of fine roots may need to be accounted for in models for systems like the one studied here. For instance, using root data based on a few samples for such a heterogeneous system may entail substantial uncertainties in results of water balance simulations for certain artificial vegetation ecosystems.…”
Section: Discussionmentioning
confidence: 88%
“…Understanding horizontal and vertical distribution of fine roots is crucial for a number of applications such as spatially distributed modelling of two-dimensional water flow and root water uptake (e.g. Vrugt et al 2001), important for the design and hydrologic performance of vegetated engineered covers (Swanson et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A key strategy to minimize the environmental and public health risks associated with hazardous wastes is the use of engineered covers (Scanlon et al 2005;Swanson et al 2003). Covers are designed to serve multiple purposes including: minimizing deep drainage into buried wastes by enhancing soil moisture storage and water loss via evapotranspiration , and supporting a stable vegetation community that closely resembles natural ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Such combined experimental and modeling approach has been used extensively by many researchers (e.g., Khire et al 1999;Scanlon et al 2002;Swanson et al 2003;Yanful et al 2003;Bussière et al 2003;). Modeling allows hypothetical cases to be run and re-run to check the sensitivity of certain parameters following calibration of the program.…”
Section: Introductionmentioning
confidence: 99%